Shared Value Creation, Creative Tourism and Local Communities Development: The Role of Cooperation as an Antecedent - Dias, Álvaro (2019)
The link between local value creation through creative tourism and local development isn´t completely understood in the literature. Specifically it is unclear how creative tourism is developed in the context of rural communities with few resources and without a clear view of the path to value creation. This research analyses cooperation as an antecedent to value creation, in the context of creative tourism, based on five cases collected in five countries through in-depth interviews with local stakeholders. Results show that communities are able to recognize their potentialities and to cooperate to create value, however they are unable by themselves to overcome barriers to entrepreneurial behaviour. Results highlight the role of external entities: consensus facilitator, guidance and access to technical and financial resources.